2023
DOI: 10.1186/s12954-023-00780-3
|View full text |Cite|
|
Sign up to set email alerts
|

Assessing feasibility of a modified same-day test-and-treat model for hepatitis C among rural people who inject drugs

Abstract: Background Despite advancements in hepatitis C virus (HCV) treatment, low uptake among hard-to-reach populations remains a global issue. The current study aimed to assess the feasibility of a modified same-day test-and-treat model in improving HCV care for people who inject drugs (PWID) living in resource-constrained rural areas. Methods A pilot study was conducted in four primary healthcare (PHC) centers in Malaysia. The model's key features inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…In this study, key portable laboratory instruments (GeneXpert®, FibroScan® and abdominal ultrasound) were transported to the community sites for screening [ 18 ]. Another study looking at same day test and treat among PWIDs in rural Malaysia used a GeneXpert® that shifted between clinics, in that study 71.1% (108/152) participants started treatment on the same day of the HCV RNA testing [ 19 ]. In our study, we demonstrated the feasibility of a simpler same day “test and treat” approach for HCV which does not require for the HCV RNA testing platform to be located on site by leveraging sample referral and coordinated peer navigation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, key portable laboratory instruments (GeneXpert®, FibroScan® and abdominal ultrasound) were transported to the community sites for screening [ 18 ]. Another study looking at same day test and treat among PWIDs in rural Malaysia used a GeneXpert® that shifted between clinics, in that study 71.1% (108/152) participants started treatment on the same day of the HCV RNA testing [ 19 ]. In our study, we demonstrated the feasibility of a simpler same day “test and treat” approach for HCV which does not require for the HCV RNA testing platform to be located on site by leveraging sample referral and coordinated peer navigation.…”
Section: Discussionmentioning
confidence: 99%
“…Following publication of the original article [ 1 ], in this article the affiliation details for Author A were incorrectly given as ‘Public Health Division, State Health Department, Alor Setar, Kedah, Malaysia’ but should have been ‘Public Health Division, State Health Department, Kuala Terengganu, Terengganu, Malaysia’.…”
mentioning
confidence: 99%